Finite element analysis and design of metal structures - Ellobody, Ehab; Feng, Ran; Young, Ben (Butterworth-Heinemann, 2014)
Traditionally, engineers have used laboratory testing to investigate the behavior of metal structures and systems. These numerical models must be carefully developed, calibrated and validated against the available physical test results. They are commonly complex and very expensive. From concept to assembly, Finite Element Analysis and Design of Metal Structures provides civil and structural engineers with the concepts and procedures needed to build accurate numerical models without using expensive laboratory testing methods. Professionals and researchers will find Finite Element A.